Postharvest handling : a systems approach. - Florkowski, Wojciech J.; Shewfelt, Robert L.; Prussia, Stanley Eugene; Banks, Nigel H. (Nigel Henry), 1955- (Academic Press, 2022)
This newly revised fourth edition of Postharvest Handling brings new and updated chapters with new knowledge and applications from postharvest research. The revised edition brings back the aspects of preharvest conditions and their effects on postharvest quality and features new chapters on the increasingly important role of transportation and logistics. It emphasizes consumers and systems thinking for postharvest chains for fresh produce. This book also explores current challenges-including oversupply, waste, food safety, lack of resources, sustainability - and best practices for systems to thrive in spite of these challenges. This unique resource provides an overview of postharvest systems and their role in food value chains and offers essential tools to monitor and control the handling process. Written by a team of experts in Postharvest Systems and Handling, this book continues to be the most practical and up-to-date resource for postharvest physiologists and technologists across the disciplines of agricultural economics, agricultural engineering, food science, and horticulture along with businesses handling fresh or minimally processed products.